The Correlation Between Consuming High-Risk Foods and Sedentary Activities with Nutritional Status at SMAN 1 Uluan of Toba Regency in 2021 - Yoseva F Simanjuntak; Rd. Halim (International Journal of Health Engineering and Technology, 2022)
Currently, Indonesian adolescents are facing three nutritional issues (triple burden of malnutrition), namely malnutrition, overweight, and micronutrient deficiencies with anaemia. This study was aimed to discover the correlation between consuming high-risk foods and sedentary activities with nutritional status at SMAN 1 Uluan of Toba Regency. A correlational study with cross-sectional design was the method used in the study. This study took 61 students of XI class as the sample selected through proportional stratified random sampling technique. The data were analysed through the Chi-Square Statistical Test. The study results indicated that the high-risk foods which were categorized as frequently consumed encompassed high-fat/high-cholesterol/fried foods (50.8%), grilled foods (55.7%), processed foods with preservatives (55.7%), flavour-enhanced foods (57.4%), soft drinks (54.1%), energy drinks (55.77%), and instant foods (63.9%). While the foods that were categorized as rarely consumed encompassed sweet foods and beverages (50.8%) and salty foods (50.8%). On the sedentary activity variable, the majority of respondents conducted sedentary activities with high intensity (>5 hours/day) (47.5%), while the nutritional status variable showed overnutrition (32.8%). According to the results of statistical test, a significant correlation between consuming high-risk foods (sweet foods and beverages (p = 0.000), salty foods (p = 0.003), high-fat/high-cholesterol/fried foods (p = 0.000), grilled foods (p = 0.004), processed foods with preservatives (p = 0.003), flavour-enhanced foods (p = 0.002), soft drinks (p = 0.003), energy drinks (p = 0.042), and instant foods (p = 0.007)) and sedentary activities (p = 0.000) with nutritional status. Good and healthy consumption patterns in addition to proper physical activities/exercises are expected.